Positive performance improvement : a new paradigm for optimizing your workforce - Gerson, Richard F. (Davies-Black Pub., 2006)
"Presenting a simple yet effective new way to improve performance, Positive Performance Improvement veers away from the prevailing focus on fixing what is wrong with workers and the workplace today - performance gaps, personal deficiencies, weaknesses in core strengths. Instead, it zeros in on what can make the most dramatic impact and ensure long-lasting improvement."